2010
DOI: 10.2334/josnusd.52.23
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo analyses of the effects of desensitizing agents on dentin permeability and dentinal tubule occlusion

Abstract: This study was done to assess the influence of the topical application of two different desensitizing agents on dentin permeability and dentinal tubule occlusion. Twenty-one rats provided 84 teeth: 36 for the in vitro and 48 for the in vivo investigation. The following agents were tested: Group 1, 2% potassium nitrate plus 2% sodium fluoride gel; Group 2, 5% sodium fluoride varnish; Group 3, 3% hydroxyethylcellulose gel (control). Cervical cavities were prepared and EDTA was applied to expose the dentinal tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 24 publications
1
21
0
8
Order By: Relevance
“…5 A rational approach to the control of pain arising from exposed dentin would thus be to block the tubules or to reduce their diameter. [5][6][7][8] Ideally, a treatment for dentin hypersensitivity, as well as for other problems, should be quick and simple. Thus, the use of special toothpastes has been largely embraced as one of the first alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…5 A rational approach to the control of pain arising from exposed dentin would thus be to block the tubules or to reduce their diameter. [5][6][7][8] Ideally, a treatment for dentin hypersensitivity, as well as for other problems, should be quick and simple. Thus, the use of special toothpastes has been largely embraced as one of the first alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…31 Earlier studies have prescribed the repeated usage of desensitizing agents to ensure higher clinical effectiveness in dentinal tubule occlusion. 13 In this study, activating the dentifrices with Er,Cr:YSGG after brushing for 6 minutes and analyzing through SEM reveals diminished tubule diameter of 660 nm as opposed to 5-day application when using dentifrice alone. The chromophore for Er,Cr:YSGG is water, hence, this laser is equally applicable for soft and hard tissue procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The success of desensitizing agents is directly proportional to its ability to seal or occlude the dentinal tubules and reduce the diameter of the opened tubules thereby decreasing the hydrodynamic pain transmission mechanism. 13 The scope of modification of causative factors in the management of dentinal hypersensitivity is one which is grossly overlooked. 14 The oral environment being dynamic, the desensitizing agent has to withstand the challenges of salivary dissolution, acid attack from microbes and food components as well as chemical, mechanical and thermal trauma to provide long-lasting pain relief for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Occluding dental tubular agents can create a barrier by precipitating proteins and calcium/ phosphate ions on the surface or within the tubule orifice. 9 The degree of desensitizing activity increases with the increase of depth of penetration, because if the penetration level is less, there is chance of removal of deposits by brushing or dietary acids, but if the penetration level is more within the dentinal tubule, the brushing or dietary acids can't easily remove it; it can occlude the dentinal tubule better and thereby give more desensitizing effect. 10 The SEM study showed a wide range of depth of penetration within the dentinal tubule.…”
Section: Discussionmentioning
confidence: 99%